Lifespan decreases with proportion of sons in males but not females of zoo‐housed tigers and lemurs. (17th May 2021) - Tidière, Morgane; Douay, Guillaume; Müller, Peter; Siberchicot, Aurélie; Sliwa, Alexander; Whipple, Mylisa; Douhard, Mathieu
Abstract: Several studies have shown higher costs of rearing sons than daughters in mammals where males are larger than females. These studies typically focus on females by examining how the offspring sex ratio during a single reproductive event affected mothers' subsequent reproduction or survival probability. Here, we examine relationships between offspring sex ratio during single or multiple reproductive events and several survival metrics in mothers and fathers, using data from zoo‐housed tigers ( Panthera tigris ) and ruffed lemurs ( Varecia sp.). Our analyses failed to reveal an overall cost of reproduction or a higher cost of sons to mothers. In male ruffed lemurs, the proportion of sons produced during early life (before 10 years old) was negatively correlated with lifespan later in life. In tigers, males with a higher proportion of sons during their lifetime had shorter lifespans. One likely mechanism is the difference in testosterone levels between males: a high concentration of testosterone can increase the proportion of sons and compromise immune function. Our results suggest studies in wild populations should address the outstanding challenge of understanding consequences of sex allocation for males, and open an opportunity to predict lifespan in an applied conservation context. Abstract : In this study, we examined the relationships between offspring sex ratio and several survival metrics in mothers and fathers, using data from zoo‐housed tigers ( Panthera tigris ) and ruffed lemurs ( Varecia sp.). We found that increasing number of sons during early life or lifetime was associated with reduced longevity in fathers, but not mothers.